Practice patterns for postoperative radiation therapy in patients with metastases to the long bones: a survey of the Japanese Radiation Oncology Study Group. (18th January 2021) - Kubota, Hikaru; Nakamura, Naoki; Shikama, Naoto; Tonari, Ayako; Wada, Hitoshi; Harada, Hideyuki; Nagakura, Hisayasu; Heianna, Joichi; Ito, Kei; Nozaki, Miwako; Tago, Masao; Fushiki, Masato; et al.
Abstract: Evidence regarding postoperative radiation therapy (PORT) for metastases to the long bones is lacking. Characterizing the current practice patterns and identifying factors that influence dose-fractionation schedules are essential for future clinical trials. An internet-based survey of the palliative RT subgroup of the Japanese Radiation Oncology Study Group was performed in 2017 to collect data regarding PORT prescription practices and dose-fractionation schedules. Responders were also asked to recommend dose-fractionation schedules for four hypothetical cases that involved a patient with impending pathological fractures and one of four clinical features (poor prognosis, solitary metastasis, radio-resistant primary tumor or expected long-term survival). Responders were asked to indicate their preferred irradiation fields and the reasons for the dose fractionation schedule they chose. Responses were obtained from 89 radiation oncologists (67 institutions and 151 RT plans) who used 22 dose-fractionation schedules, with the most commonly used and recommended schedule being 30 Gy in 10 fractions. Local control was the most common reason for preferring longer-course RT. High-dose fractionated schedules were preferred for oligometastasis, and low-dose regimens were preferred for patients with a poor prognosis; however, single-fraction RT was not preferred. Most respondents recommended targeting the entire orthopedic prosthesis. These results indicated that PORT using 30 Gy in 10 fractions to the entire orthopedic prosthesis is preferred in current Japanese practice and that single-fraction RT was not preferred. Oligometastasis and poor prognosis influenced the selection of high- or low-dose regimens.